A psychological intervention (ConquerFear) for treating fear of cancer recurrence: Views of study therapists regarding sustainability. Issue 3 (15th January 2019) - Butow, Phyllis; Williams, Douglas; Thewes, Belinda; Tesson, Stephanie; Sharpe, Louise; Smith, Allan Ben; Fardell, Joanna E.; Turner, Jane; Gilchrist, Jemma; Girgis, Afaf; Beith, Jane; ,
Abstract: Objective: ConquerFear is a metacognitive intervention for fear of cancer recurrence (FCR) with proven efficacy immmediately and 6 months post‐treatment. This qualitative study documented barriers and facilitators to the sustainability of ConquerFear from the perspective of study therapists. Methods: Fourteen therapists who had delivered ConquerFear in a randomised controlled trial completed a semi‐structured phone interview, reaching theoretical saturation. Themes from thematic analysis were mapped to the Promoting Action on Research Implementation in Health Services (PARiHS) implementation framework. Results: Participants were 13 males and one female with, on average, 14 years psycho‐oncology experience. Nine over‐arching themes were identified, falling into three domains, which when present, were facilitators, and if absent, were barriers: evidence (intervention credibility, experienced efficacy, perceived need for intervention); context (positive attitude to and capacity for survivorship/FCR care, favourable therapist orientation and flexibility, strong referral pathways); and facilitation of implementation (intervention/service fit, intervention/patient fit, and training, support, and provided resources). Conclusions: ConquerFear is a sustainable intervention in routine clinical practise. Facilitators included a sound evidence base; a receptive context; good fit between the intervention, therapist orientation, and patient need; and flexibility of delivery. Where absent, these factors served as barriers. These results have implications for enhancing uptake of psycho‐oncology interventions in routine care.